2011
DOI: 10.1186/1752-1947-5-456
|View full text |Cite
|
Sign up to set email alerts
|

Novel surgical technique for complete traumatic rupture of the pancreas: A case report

Abstract: IntroductionComplete pancreatic rupture is a rare injury. The typical mechanism by which this occurs is overstretching of the pancreas across the vertebral column during blunt abdominal trauma. The management of this injury depends on the location and extent of the injury.Case presentationA 45-year-old Caucasian woman presented with blunt abdominal trauma after she fell onto the end of a handlebar during a bicycle accident. She arrived in the emergency room with stable vital signs and an isolated bruise just a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…Isolated pancreatic injury after blunt abdominal trauma is a rare entity 3 8. In our literature review, we found only three reports presenting pancreatic injury after trauma in a football game in the past two decades.…”
Section: Discussionmentioning
confidence: 95%
“…Isolated pancreatic injury after blunt abdominal trauma is a rare entity 3 8. In our literature review, we found only three reports presenting pancreatic injury after trauma in a football game in the past two decades.…”
Section: Discussionmentioning
confidence: 95%
“…[1] For the injury to occur, the impact must be of a high velocity resulting into compression of the pancreas to the vertebral column. [2] Pancreatic injuries occur in 1-5% of all abdominal injuries due to blunt force (IPT occurring in less than 1%), with an increased occurrence -12% in abdominal injuries due to penetrating trauma and a high grade of morbidity (30-60%) and mortality (10-30%) [1][2][3][4][5][6] Pancreatic injuries involving the neck and body are approximately 65% with approximately 35% involving the head and tail. [3] Concurrent small bowel lesions occur in approximately 90% of the patients with pancreatic injury due to anatomically proximal location with duodenal lesions being most common along with injury to vascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the head of pancreas is managed by drainage and in some case by Whipple's procedure in stages. Injury to the body and tail is managed in most cases by a pancreatectomy which may be combined with a Roux-en-Y pancreatojejunostomy for decreasing the occurrence of postoperative complications such as pancreatic fistula, [6,14] and in many cases splenectomy owing to the proximity of its anatomical location. Other operative techniques reported with good results [6] such as head and neck pancreatic transection with ductal section ventral to superior mesenteric vein, that is a central pancreatectomy with a distal pancreatojejunostomy done to preserve distal pancreatic tissue to prevent disruption of the endocrine and exocrine function.…”
Section: Discussion O N M a N A G E M E N Tmentioning
confidence: 99%
“…Pancreatic trauma shows up in the 1-5% of the abdominal blunt trauma (developed as an IPT in less of 1%), this prevalence turns higher (12%) in the penetrating abdominal trauma. Morbidity and mortality are high in the pancreatic trauma (30-60% and 10-30% respectively) [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, a treatment delay of more than 24 hours, duplicates or triplicates morbidity. If the indemnity of the duct is proved, expectant actitud can be used [1,3,6]. Intraoperatory Indicators suggestive of ductal injury are: Complete transection of the pancreas, direct visualization of ductal injury, central perforation, or severe maceration [5].…”
Section: Isolated Distal Pancreatic Transection Secondary To An Abdommentioning
confidence: 99%